Seroprevalence of Toxoplasma gondii, cytomegalovirus and Epstein Barr virus in 578 tissue donors in Brazil - Felipe F. Tuon; Luciana C. Wollmann; Danielle Pegoraro; Aline M. Gouveia; Amanda P. Andrejow; Amanda T. Schultz; Camila J. Gomes; Ohana C. Novaes; Phaolla A. Salmória (Elsevier, 2019)
This study aimed to verify the prevalence of IgG antibodies for Toxoplasma gondii, CMV, and EBV in tissue donors from different regions of Brazil between February 2016 and July 2017. In this retrospective study, 578 donors were evaluated from different regions of Brazil. The seroprevalence of T. gondii was 61.2%, CMV was 93%, and EBV was 98.3%. The seroprevalence increased with age, from 27.8% in donors younger than 18 years of age to 67.6% in those older than 60 years of age (p < 0.05). The analysis of the seroprevalence of CMV and EBV showed similar percentages (>90%) among the different states, the interior and capital of Paraná state, sex, and age. The seroprevalence of CMV, EBV and TOXO is high in all groups and age in Brazilian donors of tissues. Keywords: Toxoplasmosis, Cytomegalovirus, Epstein Barr virus, Bank tissue